Papel do ómega-3 marinho nas Perturbações do Espectro do Autismo e Perturbações de Hiperatividade e Défice de Atenção - uma revisão focada na dieta das mães
Autism Spectrum Disorders (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) are two increasingly prevalent neurodevelopmental disorders. This rise appears to be associated with a higher dietary intake of n-6 polyunsaturated fatty acids (PUFAs) and lower of n-3 PUFAs. Docosahexaenoic acid (DHA), a key nutritional n-3 PUFA, is crucial for an optimal offspring's neurodevelopment through the last trimester of pregnancy. Recently, lower DHA levels have been reported in children with ASD and ADHD. The present review summarizes the main research achievements concerning the effect of maternal DHA intake in children neurodevelopment, in order to elicit its role in the prevention and mitigation of ASD and ADHD. As main finding, a low maternal marine DHA intake seems negatively affect childhood neurodevelopment. Although higher DHA status at delivery were associated with better childhood neurodevelopmental, controversial results found in prenatal supplementation raised the hypothesis that the benefits of DHA may be influenced by other factors as socio-economic background and life-style. Low maternal DHA intake, conversely appears to raise the risk and the severity of ASD or ADHD. In conclusion, an optimal maternal consumption of marine products and being breastfeed may promote some neuronal protection in offspring, confirming the essential role of DHA as a modifiable risk factor for ASD and ADHD.